Un recurso natural invisible: los acuíferos transfronterizos - Cossío Klüver, Manuel Augusto de (2019)
This text deals with water resources existing in transboundary aquifers. It highlights the global importance of water, in particular of groundwater, for human development and the sustainability of ecosystems. The abundance of this natural resource deserves a study of the legal regime that can be applied. In this regard, the development of binding and non-binding regulations applicable to the study of transboundary aquifers is reviewed. Finally, one of the international disputes that have developed around the use and exploitation of transboundary underground water resources is briefly analyzed.